"I can feel myself being squeezed and stretched, moulded and grown, and expanded in my capacity to love loudly and profoundly": Metaphor and religion in motherhood blogs. (October 2020) - Ringrow, Helen
Highlights: Faith-based motherhood blogs form part of an increasing shift towards 'digital religion' Religious motherhood blogs contain common metaphors related to motherhood, such as MOTHERHOOD IS A JOURNEY Motherhood is represented in these blogs as a difficult yet rewarding experience Abstract: This article will explore how metaphors of motherhood are used by contemporary female bloggers who are affiliated with certain faith groups. Within religious contexts especially, motherhood blogs are often seen as suitable activities for women (and for young stay-at-home-mothers in particular). Motherhood blogs, like similar female-oriented texts such as internet parenting forums, have a key role to play in terms of understanding, replicating, and/or challenging gendered norms, both online and off (cf. Mackenzie 2017b, 2018 ). This article examines two sets of so-called 'mommy bloggers' from North American Church of Jesus Christ of Latter-day Saint and Evangelical Christian backgrounds, following Knapton's (2013) work on metaphor in pro-anorexia blogs. It analyses emergent online representations of motherhood in these two internet communities whose faith groups hold similar (yet not identical) beliefs, which include beliefs about the divine calling and design of being a mother. The analysis of selected extracts from the blogs suggests an explicit foregrounding of religious elements in the Evangelical Christian blogs, whereas the religious context tends to be more subtly expressed or axiomatic for the Latter-day Saint bloggers. Common metaphors of motherhood (such as motherhood is a journey ) appear frequently in the discourse of both digital communities, presenting motherhood as a difficult yet immensely rewarding experience, and one which can be shared with others online.